Analysis of Sharia Banking Efficiency in Industry Revolution 4.0 Era - Reny Fitriana Kaban; Novita Setyawati (Universitas Pendidikan Ganesha, 2020)
This research aimed to analyze the efficiency of Sharia Banking in Indonesia for the period of 2013-201, the era of industry revolution 4.0. The research method used Data Envelopment Analysis while the data was taken from the annual report of Sharia Banking Statistic issued by Indonesia Financial Services Authority for the intended years. The input variables were the third-party fund, labor cost, and other cost while the output variables were total financings and operating income. Both with CRS and VRS model input approach, Sharia Banking in Indonesia generally already had high-efficiency value either based on years or banks. The banks who had not been in high-efficiency criteria were highly recommended learning from the benchmark banks. The result showed in general the use of technology and the internet by Sharia Banking was already appropriate, which caused their operations running efficiently.